Avaliação do uso de diferimento com capim massai em semiárido cearense. - ARAÚJO, J. F. (2012)
Resumo: A avaliação do manejo do capim-massai (Panicum maximum x Panicum infestum) em condições de diferimento pode contribuir para a reserva estratégica de forragem de qualidade para os períodos de estiagem no Semiárido brasileiro. Objetivou-se, com o presente trabalho, avaliar a eficiência agronômica e a composição bromatológica da referida gramínea em área de caatinga raleada, em dois períodos de vedação (60 e 90 dias após o corte de uniformização) e quatro épocas de utilização (30, 60, 90 e 120 dias após o término do período chuvoso). O delineamento utilizado foi em blocos ao acaso em esquema de parcelas subdivididas (2 x 4), com duas épocas de vedação (parcelas) e quatro épocas de utilização (subparcelas), com três repetições. Foram avaliados: massa seca de forragem total (MSFT), massa seca de forragem morta (MSFM), massa seca de forragem verde (MSFV), massa seca de lâminas foliares verdes (MSLF), massa seca de colmos verdes (MSCV), relação folha/colmo (F/C), altura do pasto (AP), número de folhas vivas por perfilho (F/P), densidade populacional de perfilhos (DPP), interceptação fotossinteticamente ativa (IRFA) e índice de área foliar (IAF). Também foram avaliados os teores de matéria seca (MS), matéria orgânica (MO), proteína bruta (PB), fibra em detergente neutro (FDN), fibra em detergente ácido (FDA), hemicelulose (HCEL), celulose (CEL), lignina (LIG) e digestibilidade in vitro da matéria seca (DIVMS) relativos aos componentes folha da forragem acamada e não acamada e material senescente. Em relação aos períodos de vedação, observaram-se resultados significativos somente para os componentes de biomassa do pasto (MSFT, MSFV, MSLF, MSCV, MSFM e F/C) com valores superiores para 90 dias de vedação. Pelo desdobramento da interação para MSFT, observou-se máxima produção de forragem aos 71 dias de utilização. Para MSFV e MSLF, observou-se efeito linear decrescente para 60 dias de vedação e quadrático para 90 dias de vedação. Em relação à MSCV houve significância apenas para 90 dias de vedação, com máximo estimado em 812,2 kg/ha, aos 86 dias de uso. Para MSFM, em torno dos 100 dias de utilização, verificaram-se os maiores valores. Para a relação F/C, em 90 dias de vedação, houve redução linear. Para as variáveis AP, F/P e DPP, também foram observadas reduções lineares em função da elevação do período de uso. No caso da DPP, para cada dia de rebrotação, houve diminuição de dois perfilhos/m². A IRFA e o IAF foram reduzidos com o tempo de diferimento. Houve efeito significativo de época de vedação sobre o período de utilização apenas para a %PB e %DIVMS das folhas e para a %MS e %HCEL do material senescente. O prolongamento do período de vedação do capim-massai promove elevação dos componentes de biomassa, porém compromete a qualidade do pasto devido ao aumento da biomassa de colmos. A utilização na época seca deve ser feita em até 33 dias, devido à intensificação da senescência e morte de folhas e de perfilhos após esse referencial de dias. Além disso, a utilização do capim Massai 30 dias após um período de vedação de 90 dias ainda garante um suprimento forrageiro de adequado valor nutritivo. O aumento da umidade relativa do ar e a ocorrência de precipitações pluviométricas, após restrição hídrica, estimulam a rebrotação resultando em melhoria do valor nutritivo do capim. [Deferral use of evaluation with grass Masai in Ceará semiarid]. Abstract: The evaluation of management of massai grass under conditions of deferral may contribute to the strategic reserve of forage quality for the dry periods in Northeast Brazil. Based on this assumption, the study aimed to evaluate the massai grass agronomic efficiency in an area of thinned caatinga under semiarid conditions in Brazil, in two closure times (60 and 90 days after of standardization cut, that occurred 30 days after the onset of the rainy season) and four seasons of utilizatione (30, 60, 90 and 120 days after the end of the rainy season). The experiment followed a randomized block with split plot design in a factorial 2 x 4 (2 times of fencing and 4 times of use) with three replicates per treatment. Following parameters were evaluated: total dry mass of forage (TDMF), dry mass of forage dead (DMFD), dry mass of green forage (DMGF), dry mass of green blade (DMGB), dry matter of green stem (DMGS), leaf/stem ratio (L/S), sward height (SH), stretched plant height (SPH), number of leaves per tiller, tiller population density (TPD), intercepted photosynthetically active index (IPAI) and leaf area index (LAI). They were evaluated the dry matter (% DM), organic matter (% OM), crude protein (% CP), neutral detergent fiber (% NDF), acid detergent fiber (% ADF), hemicellulose (% HCEL) cellulose (CEL%), lignin (LIG%) and in vitro digestibility of dry matter (% IVDMD) for the components of leaf fodder and senescent material. At unfolding of interaction for TDMF, there was a quadratic effect for closure time of 90 days, with the point of maximum forage yield at 71 days of use. As for DMGF and DMGB, there was a linear effect for 60 days and quadratic effect for 90 days, with a maximum reached at 49 days of use for DMGF and 33 days for DMGB. In relation to DMGS there was significant effect only for 90 days of closure with maximum estimated at 812.2 kg / ha at 86 days of use. For DMFD was observed that for both closure times the best model is the quadratic response. 102 and 100 days provided higher biomass values of DMFD, with estimates of 3000 and 4337 kg/ha to 60 and 90 closure days, respectively. For L/S ratio, it was observed that the closure time of 60 days, the model that best fitted data was quadratic, while for 90 closure days, the model that best fitted data was linear decreasing. For variables SH and SPH was observed linear decrease as the increase of utilization time with estimated values: 44.8 and 23.5 cm for SH and 97.92 and 63.63 cm for SPH on utilization times of 30 and 120 days, respectively. L/S ratio was reduced with utilization time of massai grass, with estimates of 3.04 and 1.5 leaves per tiller, with 30 and 120 days of utilization times, respectively. It was observed a linear reduction in TPD. For each day of regrowth, there was a reduction of two tillers/m². IPAI and LAI reduced with time of deferral, with estimates of 93 and 84% for IPAI and 4.79 and 3.71 for LAI considering utilization times of 30 and 120 days, respectively. The results were subjected to analysis of variance by F test and when significant portions held the unfolding applying the Tukey test (p <0.05) and regression analysis for the subplots and interactions significant (p<0,05). Statistical analyzes were performed with the aid of the software SISVAR. The increase of closure time of massai grass promotes elevation of biomass components, but compromises the quality of the pasture due to increased biomass of stems. Utilization in dry season must be made within 33 days, due to the intensification of senescence and death of leaves and tillers. The use of Massai grass 30 days after a period of 90 days of fencing ensures an adequate supply of fodder nutritional value. Climatic conditions affect on the chemical composition of Massai grass. The improvement in relative humidity and the occurrence of rainfall, after water restriction, can even improve its nutritional value.